Evolution of structural and magnetic parameters of nickel nanotubes under irradiation of Fe7+ ions - Shumskaya, A; Kaniukov, E.; Shlimas, D.; Zdorovets, M.; Kozlovskiy, A. (Eurasian Journal of Physics and Functional Materials, 2026)
This work is devoted to investigations of nickel nanotubes behavior under influence of swift heavy ion irradiation. High-energy irradiation initiates damage process inside nanostructures and can cause the appearance of new phases with interesting properties. To understand the basic principles of the evolution of structural and magnetic parameters of nanostructures under the influence of high-energy processes, detailed study of nickel nanotubes irradiated with various fluences of Fe 7+ ions was carried out.Recommended CitationShumskaya, A.; Kaniukov, E.; Shlimas, D.; Zdorovets, M.; and Kozlovskiy, A. (2020) "Evolution of structural and magnetic parameters of nickel nanotubes under irradiation of Fe7+ ions," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 2, Article 4.DOI: https://doi.org/10.29317/ejpfm.2020040204